2013
DOI: 10.1057/jphp.2013.35
|View full text |Cite
|
Sign up to set email alerts
|

Health protection in times of economic crisis: Challenges and opportunities for Europe

Abstract: STOA, the European Parliament's technology assessment body, and the European Observatory on Health Systems and Policies recently organised a workshop on the impacts of the economic crisis on European health systems. Evidence of the impact of the recent financial crisis on health outcomes is only just beginning to emerge. Data suggests that this latest recession has led to more frequent poor health status, rising incidence of some communicable diseases, and higher suicide rates. Further, available data are like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 36 publications
1
21
0
3
Order By: Relevance
“…Čeprav naredi samomor skoraj ena četrtina manj Slovencev kot na primer še pred dvema desetletjema, od leta 2010 v Sloveniji po podatkih Inštituta za varovanje zdravja (2011) ponovno beležimo porast števila samomorov. Domači in tuji strokovnjaki ta porast pripisujejo neugodnim družbenim razmeram in padcu življenjskega standarda zaradi gospodarske krize, ki je zajela svet v zadnjih nekaj letih (Groleger, 2009;Stuckler, et al, 2009;Karanikolos, et al, 2013;McDaid, et al, 2013;Korošec Jagodic, et al, 2013;Pompili, et al, 2014). Po podatkih v Sloveniji tako v zadnjem času zaradi samomora letno umre približno 436 prebivalcev, od tega 347 moških in 89 žensk, njihova starost pa je v povprečju 57 let (Kalin, 2012).…”
Section: Uvodunclassified
See 1 more Smart Citation
“…Čeprav naredi samomor skoraj ena četrtina manj Slovencev kot na primer še pred dvema desetletjema, od leta 2010 v Sloveniji po podatkih Inštituta za varovanje zdravja (2011) ponovno beležimo porast števila samomorov. Domači in tuji strokovnjaki ta porast pripisujejo neugodnim družbenim razmeram in padcu življenjskega standarda zaradi gospodarske krize, ki je zajela svet v zadnjih nekaj letih (Groleger, 2009;Stuckler, et al, 2009;Karanikolos, et al, 2013;McDaid, et al, 2013;Korošec Jagodic, et al, 2013;Pompili, et al, 2014). Po podatkih v Sloveniji tako v zadnjem času zaradi samomora letno umre približno 436 prebivalcev, od tega 347 moških in 89 žensk, njihova starost pa je v povprečju 57 let (Kalin, 2012).…”
Section: Uvodunclassified
“…While almost 25 % fewer Slovenes committed suicide than even two decades ago, Slovenia has recorded an increase in the number of suicides since 2010 according to data compiled by the Institute of Public Health (2011). Domestic and foreign experts have attributed this increase to the unfavourable social situation and the decline in the standard of living due to the economic crisis that has engulfed the world in recent years (Groleger, 2009;Stuckler, et al, 2009;Pompili, et al, 2014;Karanikolos, et al, 2013;McDaid, et al, 2013;Korošec Jagodic, et al, 2013). According to the statistics, 436 inhabitants of Slovenia die of suicide every year, of whom 347 are male and 89 are female, with the average age being 57 years (Kalin, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…5,6 This impact is not direct, and can be buffered by the degree of social protection that the state offers. 5,6,10 Some studies have reported an improvement in health status during periods of financial crisis, explained, for instance, by a reduction in smoking, drinking, and sedentary behaviours. 6,11,12 However, if governments reduce public expenditure on social welfare and health services during a recession period, the impact can be worse.…”
Section: Introductionmentioning
confidence: 99%
“…6,11,12 However, if governments reduce public expenditure on social welfare and health services during a recession period, the impact can be worse. 5,8,10 In this scenario, social support can be an important protective factor. 6 Front-line healthcare workers, such as primary healthcare professionals, are in a key position to implement new strategies, based on identified protective factors, to ameliorate the impact of the economic crisis on the population.…”
Section: Introductionmentioning
confidence: 99%
“…The Science and Technology Options Assessment (STOA) Unit at the European Parliament devoted a workshop to the question. 19 International organizations concerned with health, including the World Health Organization (WHO) and the United Nations Development program (UNDP) have proposed ways to increase the resilience of health systems to economic crisis. There are well thought out plans and excellent research on ways how to avoid negative impacts of economy on health systems.…”
Section: International Reactionsmentioning
confidence: 99%